2012
DOI: 10.3109/10641963.2012.666602
|View full text |Cite
|
Sign up to set email alerts
|

Association ofCLCNKBHaplotypes and Hypertension in Mongolian and Han Populations

Abstract: We investigated a possible association between genetic variations in chloride channel Kb (CLCNKB) gene and essential hypertension (EH) in the Mongolian and Han populations in Inner Mongolia. Our study included 414 unrelated Mongolian herdsmen and 524 Han farmers. Two tagSNPs of CLCNKB (rs945393 and rs10803414) were identified from the Chinese HapMap database based on pairwise r(2) ≥ 0.5 and minor allele frequency ≥0.05. Genotyping was performed using the PCR/ligase detection reaction assay. There was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Family aggregation of hypertension in Mongolians suggests that genetic factors might play an important role in the etiology of hypertension in Mongolians. Our previous study confirmed that the chloride channel Kb gene, CLCNKB, and the PPARγ gene are involved in the genetic susceptibility to hypertension in Mongolians (Gao et al, 2010;Su et al, 2012). Furthermore, in a small study of 385 unrelated Mongolians (158 patients with hypertension vs 227 normotensive subjects), we previously examined the association of the SLC12A3 gene with hypertension in Mongolians using nine tagSNPs of the SLC12A3 gene (rs6499858, rs2289119, rs13306673, rs2010501, rs7188995, rs7204044, rs4784733, rs8063406, and rs2304478) (Chang et al, 2011b).…”
Section: Discussionsupporting
confidence: 53%
“…Family aggregation of hypertension in Mongolians suggests that genetic factors might play an important role in the etiology of hypertension in Mongolians. Our previous study confirmed that the chloride channel Kb gene, CLCNKB, and the PPARγ gene are involved in the genetic susceptibility to hypertension in Mongolians (Gao et al, 2010;Su et al, 2012). Furthermore, in a small study of 385 unrelated Mongolians (158 patients with hypertension vs 227 normotensive subjects), we previously examined the association of the SLC12A3 gene with hypertension in Mongolians using nine tagSNPs of the SLC12A3 gene (rs6499858, rs2289119, rs13306673, rs2010501, rs7188995, rs7204044, rs4784733, rs8063406, and rs2304478) (Chang et al, 2011b).…”
Section: Discussionsupporting
confidence: 53%